Changes in quadriceps muscle thickness in acute non-ambulatory stroke survivors. Issue 1 (2nd January 2016) - Nozoe, Masafumi; Kanai, Masashi; Kubo, Hiroki; Kitamura, Yuka; Shimada, Shinichi; Mase, Kyoshi
Abstract : Background: Loss of skeletal muscle mass is one of the main reasons for disability in patients with stroke. However, lower leg muscle wasting has not been studied in acute stroke patients. Objective: To investigate the changes in quadriceps muscle thickness in acute non-ambulatory stroke survivors. Methods: A total of 16 consecutive acute non-ambulatory stroke survivors who were in acute inpatient rehabilitation, with a mean age of 72.1 years, were included in the study. Quadriceps muscle thickness was examined in their paretic and non-paretic limbs within the first week from admission (first week), 1 week after the first examination (second week), and 1 week after the second week examination (third week) using ultrasonography. Results: Quadriceps muscle thickness in the paretic limb decreased every week (mean% difference between the first and second weeks, 12.8, 95% confidence interval (CI) 5.3–20.2%; mean% difference between the second and third weeks, 10.1, 95% CI 5.2–14.9%). Quadriceps muscle thickness in the non-paretic limb was lower in the second and third weeks than the first week, but there was no difference between the second and third weeks (mean% difference between the first and second weeks, 9.3, 95% CI 2.5–16.1%; mean% difference between the second and third weeks, 5.3, 95% CI − 1.6 to 12.1%). Conclusion: Quadriceps muscle thickness decreased in acute non-ambulatory stroke survivors not only in the paretic limb but also in the non-paretic limb, particularly during the period from admission to the second week.